Epoxydisilanes by direct double silylation of terminal epoxides - Hodgson, D; Kirton, E (2004)
Terminal epoxides 2 are converted to epoxydisilanes 1 in a one-pot procedure in hexane at low temperatures, by using successive additions of Me3SiCl and s-BuLi-(-)-sparteine complex.